1996
DOI: 10.3109/15563659609013768
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Testosterone Levels in Skeletal Fluorosis Patients

Abstract: Decreased testosterone concentrations in skeletal fluorosis patients and in males drinking the same water as the patients but with no clinical manifestations of the disease compared with those of normal, healthy males living in areas nonendemic for fluorosis suggest that fluoride toxicity may cause adverse effects in the reproductive system of males living in fluorosis endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Decreased serum testosterone levels have also been reported in human population exposed to fluoride at doses of 3-27 mg/day compared with a group of individuals exposed to fluoride at low doses of 2-13 mg/day [17]. The decrease in serum testosterone observed in the present study could also be due to fluoride-induced damage of Leydig cells [18].…”
Section: Discussionsupporting
confidence: 57%
“…Decreased serum testosterone levels have also been reported in human population exposed to fluoride at doses of 3-27 mg/day compared with a group of individuals exposed to fluoride at low doses of 2-13 mg/day [17]. The decrease in serum testosterone observed in the present study could also be due to fluoride-induced damage of Leydig cells [18].…”
Section: Discussionsupporting
confidence: 57%
“…Data suggest that excessive exposure to fluoride may be associated with central nervous system and reproductive dysfunctions in humans and other animals (Spittle 1994;Spittle 2008;Chioca et al 2007). Epidemiological studies have indicated lower levels of serum testosterone in men living in fluorosis endemic areas, exposed to 1.5 -14.5 ppm F in drinking water (Susheela and Jethanandani 1996) or when exposed to 3 -27 mg F/day occupationally (Ortiz-Périez et al 2003). Studies using laboratory animals focusing the effects of fluoride on reproductive functions show conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…odourless, and free from solid suspension. The result of absorbance have been compiled below for the se samples:- Table I-Fluoride Concentration of water samples in village Baraul samples Fluoride in mg/l s1-sw 1 2.40 s1-sw 2 2.80 s1-sw 3 3.50 s1-sw 4 2.50 s1-sw 5 3.0 s1-sw 6 3.0…”
Section: Results and Disscussionmentioning
confidence: 99%
“…odourless, and free from solid suspension. The result of absorbance have been compiled below for these samples:- 1 3.16 S5-sw 2 3.18 S5-sw 3 2.50 S5-sw 4 3.0 S5-sw 5 3.50 S5-sw 6 3.20…”
Section: Water Samples Village Iii-banapattimentioning
confidence: 99%
See 1 more Smart Citation